1985
DOI: 10.1111/j.1442-9993.1985.tb00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Foraging patterns of breeding birds in eucalypt forest and woodland of southeastern Australia

Abstract: The foraging ecology of eucalypt forest and woodland birds was studied on three 10 ha plots in southeastern Australia. Quantitative data were obtained for 41 species of which 31 were insectivorous, eight were nectar-feeders, and two were parrots that fed primarily on eucalypt seeds. Birds-of-prey, large omnivores andfrugiwres were uncommon. Insectivorous birds differed in foraging behaviour, the substrates on which they found prey, and foraging height. Nectar-feeders exploited a variety of carbohydrates includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 24 publications
3
61
0
1
Order By: Relevance
“…The density of birds estimated for each transect and the mean number of birds observed for each transect were correlated (r = 0.544, d$ = 1, P = 0.004). Previous surveys of forest bird communities in Australia have indicated that older aged forest support a greater diversity and density of forest birds due to their floristic and structural complexity (Loyn 1980;Loyn & MacFarlane 1984;Kavanagh et al 1985;Recher et al 1985;Loyn 1993). Conversely, studies examining silviculturally thinned forest have suggested that lower total bird density in these forests was due to the loss of this resource complexity (Wood & Niles 1978;Saxon et al 1990;Brown et al 1991).…”
mentioning
confidence: 99%
“…The density of birds estimated for each transect and the mean number of birds observed for each transect were correlated (r = 0.544, d$ = 1, P = 0.004). Previous surveys of forest bird communities in Australia have indicated that older aged forest support a greater diversity and density of forest birds due to their floristic and structural complexity (Loyn 1980;Loyn & MacFarlane 1984;Kavanagh et al 1985;Recher et al 1985;Loyn 1993). Conversely, studies examining silviculturally thinned forest have suggested that lower total bird density in these forests was due to the loss of this resource complexity (Wood & Niles 1978;Saxon et al 1990;Brown et al 1991).…”
mentioning
confidence: 99%
“…The value of Lantana to a range of bird species both as a foraging and shelter location has previously been demonstrated (Crome et al 1994). In the present study, as Superb Fairy-wrens forage largely on, or very close to, the ground (Tidemann 1983;Recher et al 1985;Ford et al 1986;Cale 1994), it is likely that Lantana is providing the birds with a dense and protective understorey layer rather than a foraging site. The use of Lantana by foraging insectivorous birds has not been investigated previously.…”
Section: Discussionmentioning
confidence: 65%
“…Many studies since MacArthur's have shown that bird communities actually consist of groups or sets of species with similar resource utilisation patterns (Recher et al 1985;Holmes and Recher 1986;Ford et al 1986;Mac Nally 1994). Members of these groups often have similar foraging behaviours and are referred to as guilds (Root 1967) or functional groups (Cummins 1973).…”
Section: Introductionmentioning
confidence: 99%